Effects of Metaverse Technology and Drone Delivery: Online Mobile Accessories Shopping in a Virtual Shop - Jayathilaka, Ravindu; Samarasinghe, Sadisha; Parami Jayasekara; Batawala, Randika; D. I. De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
In the busy world most people don't have time for shopping. So, in that situation online shopping is more popular in many countries including sri lanka. So, we intend to use the metaverse technology to make mobile accessories shopping easier in our busy life by this research. In addition, we also intend to introduce an improved drone delivery system through this research so, in the future we have an idea to develop our previous web application by using metaverse technology and drone delivery system. As the functions of our previous web application, we used manage user profile, manage accessories, purchase order part, add to cart part, manage delivery and manage feedback & complaints. This research paper discusses the creation of a virtual world in a way that appeals to the customer while using the metaverse technology and how to provide the customer with the experience of shopping from home in the future. Furthermore, through this research, the problems that occur while shopping in shopping malls are predicted. It aims to provide a superior shopping experience by reducing transaction costs. This type of research is useful for the development of the future e-commerce industry.